A Systematic Literature Review: Performance Pathways and Firm Performance Implications - Ismail, Gurawan Dayona; Arifin, Aidil; Maulana, Yusup; Rahman, Ardiyatur; Widharsana, Stevanus Dwi Citra (Dinasti International Journal of Management Science, 2026)
It has long been known that leadership plays a crucial role in determining both organizational success and worker performance. Scholarly interest in comprehending how leadership affects employee productivity and how these individual level results transfer into company success has been rekindled in recent years due to increased global rivalry, digital change, and post-pandemic work arrangements. In order to compile empirical data on the relationship between leadership, employee productivity and performance, and organizational or company performance, this study does a systematic literature review (SLR) of worldwide peer-reviewed journal publications published between 2020 and 2025. Using the PRISMA 2020 technique as a guide, 68 outstanding studies were located and submitted to thematic synthesis analysis. According to the review, employee performance and productivity are continuously positively correlated with leadership styles, especially transformational, servant, ethical, inclusive, empowering, and strengths-based leadership. However, psychological, relational, and behavioral mechanisms like job engagement, motivation, trust, leader-member interchange, and organizational identification influence these benefits, which are primarily indirect. Although there is some evidence, it is still dispersed and mostly comes from multi-level or branch-level research that show a substantial correlation between staff productivity and firm-level performance. In addition to highlighting important research gaps, such as the absence of longitudinal designs, inconsistent productivity measurements, and a dearth of multi-level studies, this review suggests an integrative performance pathway model. The significance of leadership development systems that institutionalize engagement and alignment methods to translate employee performance increases into long-term company performance is highlighted by practical consequences.